2020
DOI: 10.1080/23322039.2020.1790964
|View full text |Cite
|
Sign up to set email alerts
|

Environmental accounting practices and cost of capital of enterprises in Vietnam

Abstract: This study aimed to investigate the nexus between the level of environmental financial accounting practices (EFAP) and cost of capital. The population of this study is 1.188 firm-year observations. However, we excluded 408 firm-year with less than 2 years of information to calculate EFAP, 73 firm-year without sufficient financial accounting information to calculate the cost of capital and 35 firm-year without sufficient financial accounting information to calculate control variables. Finally, this paper used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…In similar vein, Piechocka-Kaluzna et al (2021) reported significant negative correlation between ESG and its sub dimensions and cost of finance. Huu Anh et al (2020) reported evidence that firms disclosing more accounting information related to environmental issues tend to have lower cost of finance than those who do not. Palea and Drogo.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In similar vein, Piechocka-Kaluzna et al (2021) reported significant negative correlation between ESG and its sub dimensions and cost of finance. Huu Anh et al (2020) reported evidence that firms disclosing more accounting information related to environmental issues tend to have lower cost of finance than those who do not. Palea and Drogo.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many previous studies related to the cost of capital have been carried out include governance (AlHares, 2020; Arslan, 2019;Khan et al, 2020;Pham et al, 2012), litigation risk (Qin et al, 2020), corporate social responsibility disclosure (Atan et al, 2018;Ellili, 2020;Gjergji et al, 2021;Johnson, 2020;Rahmasari, 2013), economic policy uncertainty (Xu, 2020), risk disclosure (Almania, 2019;Liu, 2020), leverage (Battisti et al, 2020;Rajverma et al, 2019), environmental disclosure (Anh, 2020;Haninun et al, 2019), integrated reporting (Vena et al, 2019), ownership structure (Rajverma et al, 2019), dividend policy (Rajverma et al, 2019), disclosure quality (Ezat, 2019), intellectual capital disclosure (Gomes et al, 2019), employee shareholding (Aubert et al, 2017), information risk (Safdar & Yan, 2016), earnings management (Patro & Kanagaraj, 2016), board of directors concentration (Upadhyay, 2014), excess control (Bozec et al, 2014), and earnings quality (Apergis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%